Bringing us back - Dhliwayo, Mercy (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My thesis takes the form of a collection of short stories set mostly in Zimbabwe and South Africa under the current political, social and economic climate. The themes I explore include forced migrations, identity, family disintegration and destitution. I use non-linear narration inspired by my reading of Dambudzo Marechera and Lidia Yuknavitch's use of photographic imagery, in Black Sunlight and The Small Backs of Children respectively, to heighten my thematic concerns. The poetry in their language also serves as a source of inspiration, as does the graphic imagery used by Ayi Kwei Armah. In addition, I draw on the fragmented form used by Deepak Unnikrishnan to explore migration in his collection, Temporary People and Miljenko Jergovic's investigation of violence and displacement in Sarajevo Marlboro.
Keywords: South African fiction (English) -- 21st century; Short stories, South African (English) -- 21st century